2013
DOI: 10.3329/cbmj.v2i1.14190
|View full text |Cite
|
Sign up to set email alerts
|

Post partum diastasis of the pubic symphysis: a case report

Abstract: The post partum diastasis ( means separation) of pubic symphysis is an uncommon disease. It causes acute pelvic pain. Manual pressure to the pelvis in a latero-lateral and antero-posterior direction worsens the condition. The diagnostic test for this condition is an anteroposterior X-ray of the pelvis. Here we present a case following spontaneous vaginal delivery. The conservative treatment is able to obtain good results. If this disease is underestimated the patient can develop chronic pain.CBMJ 2013 Jan:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…MRI discovers abnormalities in the pubic area during pregnancy [9] . Although many previous studies have showed changes and separation of the pubic symphysis [10] , [11] , [12] , [13] , [14] , few data are available on changes of sacroiliac joints [ 8 , 15 , 16 ]. We assessed pelvic alignment and sacroiliac joints using a three-dimensional (3D) pelvic model based on MRI in a pregnant woman during gestational weeks 28 – 39, and at 4 and 72 weeks after childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…MRI discovers abnormalities in the pubic area during pregnancy [9] . Although many previous studies have showed changes and separation of the pubic symphysis [10] , [11] , [12] , [13] , [14] , few data are available on changes of sacroiliac joints [ 8 , 15 , 16 ]. We assessed pelvic alignment and sacroiliac joints using a three-dimensional (3D) pelvic model based on MRI in a pregnant woman during gestational weeks 28 – 39, and at 4 and 72 weeks after childbirth.…”
Section: Introductionmentioning
confidence: 99%